Controllable Fabrication of Networked Three-Dimensional Nanoporous Anodic Alumina Films on Low-Purity Al Materials. Issue 1 (1st January 2015) - Kure-Chu, S.-Z.; Osaka, K.; Yashiro, H.; Segawa, H.; Wada, K.; Inoue, S.
Abstract : Networked three-dimensional (3D) nanoporous alumina nanostructures—consisting of vertical cylindrical stem pore arrays (170–310 nm in diameter) and periodical transverse branched pores (20–80 nm in diameter) interspaced regularly by 190–220 nm across the vertical pore walls—were controllably fabricated from low purity Al materials (99.0%, 99.3%, and 99.56%) by anodization in a phosphoric acidic solution at 110–190 V. The formation of transverse pores depended predominantly on the purity of the Al base materials and the corrosion resistance of the anodic porous alumina films, which can be mainly attributed to anodic and/or chemical dissolution of impurities such as Fe, Cu, Zn, Mg, and Mn incorporated in the Al base materials. Moreover, the effects of the purity of Al materials on the growth and morphology of porous alumina films in oxalic and sulfuric acid solutions were also investigated by a two-step anodization of Al sheets with different purities, namely 99.0%, 99.3%, 99.56%, and 99.999% Al. The alumina films grew more slowly in all electrolytes with decreasing Al purity, which can be attributed to the lower corrosion resistance of the PAA films containing small quantities of Fe oxides and/or hydroxides produced during anodization.